Knowledge and Perception of Child Maltreatment among Parents of Under 18 children in a Metropolitan City: A Cross-Sectional Study - Saagarika Ayappan; Dinesh Kumar Ganesan; Timsi Jain (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Child maltreatment is the abuse and neglect that occurs to children under 18 years of age. It includes all types of physical and/or emotional ill-treatment, sexual abuse, neglect, negligence and commercial or other exploitation. Objective: To assess the Knowledge and perception of Child maltreatment among parents of Under 18 children. Method: This was a Cross-Sectional Study done among parents of paediatric patients (aged under 18 years) who attended a private tertiary level hospital. A total of 324 selected parents were interviewed during the study period. The study was conducted in the form of a questionnaire which consisted of 3 parts. Results: In the study 96.2%of the parents who participated were aware of the term "child abuse" but among them, 6.1% were unaware of the fact that there are different types of abuse. More than 2/3rd (76.85%) of the parents felt that alcohol influences the behavior of predators of child abuse. Overall, age, education level, and marital status were the statistically significant factors in the current study. Conclusion: The parents in our society today are aware of what child abuse is and its influence on children, society, and the community in general but the knowledge related to legislations have to improve.